2019
DOI: 10.1002/adfm.201806278
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Cu‐Cone‐Shaped Cation Source Inserted Conductive Bridge Random Access Memory and Its Improved Switching Reliability

Abstract: Conductive bridge random access memory (CBRAM) has been regarded as a promising candidate for the next-generation nonvolatile memory technology. Even with the great performance of CBRAM, the global generation and overinjection of cations after much repetitive switching cannot be prevented. The overinjection of cations into an electrolyte layer causes high-resistancestate resistance (R HRS ) degradation, on/off ratio reduction, and eventual switching failure. It also degrades the switching uniformity. In this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 61 publications
0
43
0
Order By: Relevance
“…The V th distribution of S 3 ‐TS was very tight, ranging from 0.85 to 1.14 V. This can be attributed to the localization of the TS operation due to the concentration of the electric field from the residual CF as seed in the porous HfO 1.91 buffer layer, as well as the control of the injection of Ag ions from HfO 1.91 as a buffer and dense HfO 2 as an active selector. [ 40 ] In addition, the standard variation of V th increased from 0.07 to 0.14 as the thickness of HfO 2 increased from 0.5 to 1 nm, as shown in Figure 5c. The variation in the CF length in the thick electrolyte was wider than that in the thin electrolyte, leading to a V th distribution based on the electrolyte thickness.…”
Section: Resultsmentioning
confidence: 89%
“…The V th distribution of S 3 ‐TS was very tight, ranging from 0.85 to 1.14 V. This can be attributed to the localization of the TS operation due to the concentration of the electric field from the residual CF as seed in the porous HfO 1.91 buffer layer, as well as the control of the injection of Ag ions from HfO 1.91 as a buffer and dense HfO 2 as an active selector. [ 40 ] In addition, the standard variation of V th increased from 0.07 to 0.14 as the thickness of HfO 2 increased from 0.5 to 1 nm, as shown in Figure 5c. The variation in the CF length in the thick electrolyte was wider than that in the thin electrolyte, leading to a V th distribution based on the electrolyte thickness.…”
Section: Resultsmentioning
confidence: 89%
“…From the microscopic point of view, the stochasticity in the formation of the CF induces the nonuniformity in . In this regard, many efforts have been made to reduce this nonuniformity: Li et al showed that utilizing copper ions over silver ions improves the uniformity in CB-RAM because of the faster diffusion of the former 18 , whereas Kim et al used a cone-shaped Cu-ion source in CB-RAM 19 . Niu et al engineered field crowding using a narrow bottom electrode, whose edge forms a field-crowding location and in turn a CF growth site, to improve the stability of a HfO 2 ReRAM 20 .…”
Section: Resultsmentioning
confidence: 99%
“…It is found that constructing metal pyramidal electrode, nanocone electrode, or inserting metal nanodots can concentrate the electric field in a confined region and thus guide the growth of CFs. [ 17,101,119–121 ] As shown in Figure 4d, the electric field is highly concentrated between the tip end of the Ag nanocones and SiO 2 , which serves to guide the formation of CFs. [ 17 ] In addition to constructing different structures in the memristor, the uniform resistive switching parameters can also be achieved by maximizing the uniformity of resistive materials.…”
Section: Key Requirements and Progress For Large‐scale Memristor Cbasmentioning
confidence: 99%